Sustainable budget allocation strategy in supporting SDGs environmental pillar in Malang City, Indonesia - Aini, Asfa Agustina Nusba; Rahmawati, Farida; Sumarsono, Hadi (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2024)
Sustainable Development Goals (SDGs) consist of three pillars: economic, social and environmental. It has been observed that the environmental pillar in Malang City has declined, while the economic and social pillar have increased, indicating that economic and human activities in general have a big influence on reducing environmental quality. This research focuses on evaluating sustainable budget allocation strategies that support the environmental pillar. Budget efficiency analysis was used to assess SDGs achievement in Malang City from 2019 to 2022. Based on the calculation results of this research, Malang City's budgeting efficiency was in the "very poor" category during the 2019-2022 period. It was also observed that the best budget allocation strategy occurred in 2022. In addition, this research shows that the budget allocation strategy is sorted based on the immediacy of need into four budget allocation priorities. The priority grouping can be used as a sustainable budget allocation strategy, especially in the event of limited budget. From a socio-economic point of view, government policy is also a contributing factor with a negative impact on the environment. Therefore, it is hoped that the sustainable budget allocation strategy can serve as a solution to continue paying attention to and improve environmental quality while growing the economy.JEL ClassificationÂ H72; Q51; R58